1991
DOI: 10.1103/physreva.43.4771
|View full text |Cite
|
Sign up to set email alerts
|

L-subshell fluorescence yields for elements with 73≤Z≤83

Abstract: An analysis of the I x-ray spectra, induced by -50 keV electron impact and recorded with a curved crystal spectrometer, has been performed based on a calculation model that takes into account all physical events taking place during the initial ionization and inner-vacancy processes. The L-subshell fluorescence yields co&, co&, and co3 for ten elements with atomic number Z =73-83 were obtained. They are all in good agreement with recent measurements but display an appreciable disagreement with the semiempirical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
75
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 63 publications
3
75
3
Order By: Relevance
“…The ratios of fluorescence yields, ω 1 /ω 2 , ω 1 /ω 3 and ω 2 /ω 3 , deduced from the present work are compared with those measured by Werner and Jitschin, 9 Xu 10 and Sogut et al 12 in Table 6. The ω 1 /ω 3 and ω 2 /ω 3 ratios are lower by ¾22 and ¾12%, respectively, than the earlier measured values for Au, 9,10 Hg 10 and Tl. 10 Keeping in mind the consistency of the ω 3 values from different sets, it is concluded that both the ω 1 and ω 2 values from the present work are lower than the earlier measurements.…”
Section: Resultscontrasting
confidence: 76%
See 2 more Smart Citations
“…The ratios of fluorescence yields, ω 1 /ω 2 , ω 1 /ω 3 and ω 2 /ω 3 , deduced from the present work are compared with those measured by Werner and Jitschin, 9 Xu 10 and Sogut et al 12 in Table 6. The ω 1 /ω 3 and ω 2 /ω 3 ratios are lower by ¾22 and ¾12%, respectively, than the earlier measured values for Au, 9,10 Hg 10 and Tl. 10 Keeping in mind the consistency of the ω 3 values from different sets, it is concluded that both the ω 1 and ω 2 values from the present work are lower than the earlier measurements.…”
Section: Resultscontrasting
confidence: 76%
“…The ω 1 /ω 3 and ω 2 /ω 3 ratios are lower by ¾22 and ¾12%, respectively, than the earlier measured values for Au, 9,10 Hg 10 and Tl. 10 Keeping in mind the consistency of the ω 3 values from different sets, it is concluded that both the ω 1 and ω 2 values from the present work are lower than the earlier measurements. 9,10 The present ω 1 /ω 2 ratios are ¾18 (21) and ¾11% lower than the earlier measured values for Au and Hg, respectively, and exhibit good agreement for Tl.…”
Section: Resultscontrasting
confidence: 76%
See 1 more Smart Citation
“…This event causes an increase in the L x-ray emission probability and a decrease in the Auger electron emission probability. As seen from Table 1, the values of ω 1 /ω 2 , ω 1 /ω 3 and especially ω 2 /ω 3 are in good agreement with those of Xu 17 and Puri et al 23…”
Section: Resultssupporting
confidence: 84%
“…These differences arise from the production cross-section values which are used to calculate the average Lshell fluorescence yields and theω 3 sub-shell fluorescence yields. L and M shell X-ray fluorescence parameters are more complicated than the K shell parameters because spectral lines of L and M shell are dependent not only on the cross sections of the various subshell but also on the Coster-Kronig transitions (Wu et al (2007), Xu (1991)) pointed out about the effect of multivacancy on the L X-ray fluorescence yields and it was concluded that both fluorescence yields and X-ray intensity ratios of multiple ionized atoms can be significantly different from those of the singly ionized atoms and vary with the number and configuration of vacancies. Multiple ionization of the atom might be a potential source of observed changes on the L X-ray fluorescence parameters.…”
Section: Resultsmentioning
confidence: 99%